Solid Waste Management and Recycling Actors, Partnerships and Policies in Hyderabad, India and Nairobi, Kenya - Baud, Isa.; Post, Johan; Furedy, Christine; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2004)
This book is for practising professionals and academics working in urban planning and international development: international project staff, trainers, urban development researchers and teaching staff in universities and polytechnics. Solid Waste Management and Recycling is unique in that it: -utilizes an 'integrated solid waste management perspective' in its analysis; -provides embedded case study data; -deals with both formal and informal actors and institutional arrangements in solid waste management and recycling; -has chapters written by experts from the countries concerned (Kenya and India); -can be used in graduate-level courses in urban development, urban management and planning, and technical engineering courses for students, project staff, and technical students.
Markets, partnerships and sustainable development in solid waste management; raising the questions -- Markets, partnerships and sustainable development in solid waste management; raising the questions -- Collection, Transportation and Disposal of Urban Solid Waste -- Evolving partnerships in the collection of urban solid waste in the developing world -- Collection, transportation and disposal of urban solid waste in Hyderabad -- Collection, transportation and disposal of urban solid waste in Nairobi -- Trial and error in privatisation; the case of Hyderabad$1 (Bs solid waste management -- Reuse, Recovery and Recycling of Urban Inorganic Solid Waste -- Reuse, recovery and recycling of urban inorganic solid waste; modalities, commodity chains and sustainable development -- Reuse, recovery and recycling of urban inorganic solid waste in Hyderabad -- Reuse, recovery and recycling of urban inorganic solid waste in Nairobi -- Reuse of Urban Organic Solid Waste -- Urban organic solid waste: reuse practices and issues for solid waste management in developing countries -- Urban organic solid waste: practices in Hyderabad -- Demand for compost from urban organic solid wastes in Hyderabad -- Urban organic solid waste: practices in Nairobi -- Conclusions -- Government, market and community in urban solid waste management; problems and potentials in the transition to sustainable development.s
Keywords: Air pollution; Environmental management; Geography; Atmospheric Protection/Air Quality Control/Air Pollution; Environmental Management; Geography, general